2009
DOI: 10.1603/022.038.0622
|View full text |Cite
|
Sign up to set email alerts
|

Determining Circadian Response of Adult MaleAcrobasis nuxvorella(Lepidoptera: Pyralidae) to Synthetic Sex Attractant Pheromone Through Time-Segregated Trapping With a New Clockwork Timing Trap

Abstract: Mate finding is a key lifecycle event for the pecan nut casebearer, Acrobasis nuxvorella Neunzig, as it is for virtually all Lepidoptera, many of which rely on long-range, species-specific sex pheromones, regulated largely by circadian clocks. Adult male moths were trapped at discrete time intervals during the first two seasonal flights for 6 yr to determine times of peak activity associated with male response to pheromones. From 1997 to 2002, the Harris-Coble automated clockwork timing trap was used for hourl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Higher PNC gene copies in the feces of bats captured in the evening than bats captured in the morning contradicts our expectations based on male moth activity patterns in other studies. Although male PNC moths are responsive to pheromones during the entire scotophase (22:00-05:00), the majority of trap captures and peak female mate calling typically occurs between 00:00 and 04:00 [25,75]. Our results suggest that PNC flight activity may be higher in the evening hours than that indicated by pheromone traps.…”
Section: Temporal Predator-prey Patternsmentioning
confidence: 60%
See 1 more Smart Citation
“…Higher PNC gene copies in the feces of bats captured in the evening than bats captured in the morning contradicts our expectations based on male moth activity patterns in other studies. Although male PNC moths are responsive to pheromones during the entire scotophase (22:00-05:00), the majority of trap captures and peak female mate calling typically occurs between 00:00 and 04:00 [25,75]. Our results suggest that PNC flight activity may be higher in the evening hours than that indicated by pheromone traps.…”
Section: Temporal Predator-prey Patternsmentioning
confidence: 60%
“…With the advent of molecular analyses of fecal DNA, our ability to characterize [27], with minimal dispersal outside of the orchards [28]. They are most active around pecan nuts, and are present in orchards for only 2-3 weeks during each generation [25]. Two to four generations of PNC larvae feed on pecan nuts during each growing season, and the pest overwinters as immature larvae in pecan shoots [27].…”
Section: Introductionmentioning
confidence: 99%
“…In some taxa, there is selection on larger male body size (Wiklund & Forsberg 1991;Blanckenhorn 2005) due to increased competitive ability in contests or due to female preference for larger males (Hedrick & Temeles 1989). However, the most common form of competition between male moths is likely to occur as scramble competition (Wickman 1992;Stevenson & Harris 2009), which in many taxa selects for smaller male body size (reviewed in Herberstein et al 2017) such as that found in Izatha. Protandry has been proposed to be interrelated with female-biased sexual size dimorphism as suggested by the constraint hypothesis (Wiklund & Solbreck 1982;Morbey & Ydenberg 2001).…”
Section: Male-biased Sex Ratios Protandry and Sexual Size Dimorphismmentioning
confidence: 99%
“…Lastly, unnatural light conditions are also likely to affect reproductive behaviors in butterflies due to the timing that males begin patrolling for females. Mate finding behaviors in several species of moths and butterflies are dependent upon time of day and most likely entrained by light conditions [ 97 , 103 , 130 , 131 ]. And several species of butterflies have consistent eclosion times after sunrise that correspond to mate-locating behaviors [ 98 ].…”
Section: Unnatural Lighting Implications For Butterfliesmentioning
confidence: 99%